Circumventing challenges in mitochondrial targeting for cancer treatment: leveraging nanoplatforms for effective solutions - Pandya, Shivani R. (2024)
Cancer is a highly complex disease that affects lives and causes millions of deaths worldwide. Several approaches are currently employed as cancer treatment options. Among them, mitochondrial targeting offers a highly promising approach to precise cancer treatment. Indeed, various engineered nanomaterials loaded with chemotherapeutic drugs were developed to precisely target mitochondria. This review investigates the challenges of cancer treatment, particularly in photodynamic, photothermal, and chemotherapies. Drawing on insights from mitochondrial biology and targeting materials, it unravels the complex connection between cancer, mitochondria, and nanoplatform-based targeted therapy. The attention is specifically on nanoparticles and their emerging role in precisely targeting mitochondria, offering solutions for effective treatment of cancer.